Advanced engineering electromagnetics - Balanis, Constantine A., 1938- (Hoboken, N.J. : John Wiley & Sons, 2012)
"Balanis' new edition of Advanced Engineering and Electromagnetics features new content on the basics of Metamaterials including figures to demonstrate their properties. Several small sections have been added on Mie series scattering by a PEC sphere; wedge diffraction by a wedge with surface impedances; and curve surface diffraction. Throughout the book, there are more helpful examples, end-of-chapter problems, and references as well as lecture notes in PowerPoint format. The revised edition also features MATLAB programs to animate some of the wave phenomena such as: propagation, reflection and refraction by planar interfaces; scattering by PEC circular cylinder, dielectric circular cylinder, dielectric coated PEC circular cylinder, and PEC sphere; and wedge defraction by 2-D PEC wedge"--
Includes bibliographical references and index.
Keywords: Electromagnetism; SCIENCE / Electromagnetism